Optimisation of Photocatalytic Degradation for Enhancing Bathroom Greywater Quality Using 2,4,6-Trinitrotoluene/Zeolite Photocatalyst - Siti Nor Hidayah Arifin; Paran Gani; Radin Maya Saphira Radin Mohamed; Adel Al-Gheethi; Chin Wei Lai; G. Yasni; Kean Hua Ang (Tecno Scientifica Publishing, 2026)
This experimental study investigated the solar photocatalytic degradation process for improving bathroom greywater quality using titanium dioxide nanotubes modified 2,4,6-trinitrotoluene with zeolite (TNTs/zeolite) and sought to optimize it. Organic pollutants, suspended solids, and personal care products remained in total household greywater at a proportion of 43–70% from bathroom sources. The optimization method applied was Central Composite Design (CCD) under Response Surface Methodology (RSM), in which three independent variables were considered: pH within a range of 3–10; catalyst loading expressed as the exposed surface area of 1 or 2 cm²; and irradiation time between thirty and one hundred eighty minutes under natural sunlight conditions with average irradiance values between six hundred twenty and seven hundred eighty watts per square meter. Twenty runs were carried out in triplicate. The responses tested were Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), turbidity, pH, and Dissolved Oxygen (DO). The optimum condition predicted by RSM had a pH of 6.25, an irradiation time of 180 minutes, and a catalyst loading of 1 × 1 cm². Experimental validation at this optimum condition confirmed the adequacy of the model, with removals greater than 50% for COD, BOD, TSS, and turbidity. ANOVA showed that the models were statistically significant (p < 0.0001) and highly predictively reliable (R² > 0.90 for most responses). The study demonstrated that TNTs/zeolite under natural sunlight represented a potential low-energy alternative for bathroom greywater treatment with practical possibilities for decentralized reuse applications.